Pengembangan Perangkat Pembelajaran Model Inkuiri Terbimbing Berbantuan Simulasi PhET Untuk Meningkatkan Keterampilan Proses Sains Peserta Didik - Siti Maryam Ulfa; Jannatin 'Ardhuha; Hairunnisyah Sahidu (Department of Physics Education, Universitas Mataram, 2022)
This research aimed to produce products in the form of a guided inquiry model learning device assisted by PhET simulation that is feasible, practical and effective to improve students' science process skills. The products developed were syllabus, Lesson Plan (RPP), teaching materials, Student Worksheets (LKPD) and test instruments for science process skills. The materials used were work and energy. The research subjects were 30 students in even semester academic year 2021/2022. The Research and Development with a 4D development model developed by Thiangaraja (1974) consisting define, design, develop and disseminate applied in this research. Data collection techniques used were validation sheets, teacher and students’ response of questionnaires related to the implementation of learning, and test instruments for science process skills. The results of the analysis showed that the learning tools are valid. The average score is 76.65% in the valid category, 93.35% in the very valid and 93.80% is categorized as reliable category. Furthermore, the level of learning implementation assessed by teachers and students was 90.30% and 81.73% with a very practical category. The results of the N-gain test of students' process skills were 50.61% in the medium category and less effective. Thus, it can be concluded that the guided inquiry model learning tool assisted by PhET simulation developed is feasible, practical and less effective for improving students' physics science process skills.